Complementary Thyroid Elastography on Conventional Ultrasound in Diagnosis of Malignant Thyroid Nodules - Muhammed, Adi Syazni; Abdullah Suhaimi, Shahrun Niza; Abdul Rashid, Nor Faezan; Md Isa, Nurismah; Shah, Shamsul Azhar (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Ultrasound has been widely used to assess thyroid nodules. Although ultrasound elastography has been developed to improve detection of thyroid malignancy, it has received mixed responses. This study aimed to determine the efficacy of ultrasound elastography in detecting malignant thyroid nodules. MATERIALS AND METHODS: Patients with thyroid nodules were assessed using conventional ultrasound and elastography followed by fine-needle aspiration and or hemithyroidectomy. The ultrasound findings were compared with the cytology or histopathology for statistical analysis. RESULTS: Out of 156 nodules from 92 patients included in the study, 12 (7.7%) were malignant and 144 (88.8%) were benign. The elastography was found to be an independent predictor of malignancy (OR 10.35, 95% CI [1.31, 81.6], p = 0.03). Other independent predictors were taller shape and central Doppler pattern obtained using conventional ultrasound. A combination of the three independent predictors was shown to improve the sensitivity of detecting malignant thyroid nodules up to 100%, 95% CI [73.5,100] with NPV of 100%. A new scoring system incorporating the three variables was developed and an algorithm using the scoring system was proposed. CONCLUSION: Thyroid elastography is an independent predictor of thyroid malignancy. Its performance is comparable to conventional ultrasound when used alone and improved when used in combination with conventional ultrasound. It is valuable as screening and risk-stratification tools for patients with thyroid nodules.